PENGARUH LIMBAH BAUKSIT SEBAGAI PENGGANTI PASIR TERHADAP KUAT TEKAN DAN DAYA SERAP BATAKO: PENGARUH LIMBAH BAUKSIT SEBAGAI PENGGANTI PASIR TERHADAP KUAT TEKAN DAN DAYA SERAP BATAKO - Alif, Meta; Hariyani, susi; Arif, robby Mauludy (Jurusan Teknik Sipil Polnep, 2022)
Bauxite waste is a result of the alumina extraction mining process; this waste has the potential to pollute the environment if it is not managed properly. One of the efforts to manage that is to utilize the bauxite waste as a substitute material for making bricks. This study uses an experimental method by replacing a mixture of bricks, it is the sand substitute with bauxite waste with the percentage of bauxite waste at 0%, 25%, 50%, 70%, and 100% of the sand requirement. In this study the sample will be made like solid brick with size 0.39 m x 0.09 m x 0.10 m. Tests in this study include compressive strength test, water absorption capacity, and economic value. The results showed that is variation 1 pc : 100% sand : 0% bauxite waste had the highest average compressive strength value was 38.5 kg/cm2, and is variation of 1 pc : 0% sand : 100% bauxite waste is the lowest average compression strength was 12.2 kg/cm2 with 28 days of age. The highest water absorption capacity is variation 1 pc : 0% sand : 100% bauxite waste with an average value was 23.73%, and variation 1 pc : 100% sand : 0% bauxite waste has the lowest water absorption capacity with an average value was 7.54%.